Palm Kernel Shell as Potential Adsorbent for Treatment and Decolorization of Palm Oil Mill Effluent (POME) - Mohammad, Nur Qurratu'ain; Abdul Hamid, Nor Hazren (Progress in Engineering Application and Technology, 2024)
The issue of POME is an important concern in Malaysia as a result of the extensive production of palm oil. The substantial quantity of Palm Oil Mill Effluent (POME) created from the manufacturing of palm oil presents a notable environmental predicament in Malaysia. This is due to the fact that POME is a liquid with a high concentration of organic matter, which poses a significant threat to the environment. Unresolved discharge of Palm Oil Mill Effluent (POME) will result in significant issues, either directly or indirectly. Therefore, activated carbon derived from palm kernel shells (PKS) was utilized in this work for the treatment of palm oil mill effluent (POME). The adoption of this approach was undertaken in order to accomplish three specific objectives of this study. To begin with, parameters were analyzed for BOD, COD, pH, turbidity, and decolorization conditions for POME. The next goal was the evaluation of the sorption kinetics and the equilibrium isotherms. Finally, the re-usability of PKS as a potential adsorbent for treating and decolorizing POME was determined. The investigation employed an adsorption procedure in which the PKS was thoroughly cleaned and physically activated in a 500°C oven before being ground into a powder with a particle size of 150 microns. The adsorption process started by mixing the powdered PKS with a dosage range of 10g to 30g into the POME with different concentrations, which are 100%, 90%, and 80%, respectively. The adsorption process was carried out for a duration of 60 minutes, 120 minutes, and 180 minutes using an orbital shaker with a 110 rpm agitation rate. The maximum percentage elimination of BOD, COD, pH value, turbidity, and color is 69.83%, 41.5%, 10.5%, and 43.7%, respectively. PKS have a significant capacity to eliminate organic pollutants and color in POME. The PKS, which is the raw material found in the palm oil mill, can be transformed into activated carbon and utilized as a sustainable method for treating POME.